Letter from Oscar D. Plomer to the Editor - British Worker, 6 May 1926, re: allegations of victimisation at University College (page 2)
1926-05-06 "Letter from Oscar D. Plomer to the Editor - British Worker, 6 May 1926, re: allegations of victimisation at University College (page 2)" [g0729002.jpg], 6 May 1926, Plomer, Oscar D